2009
DOI: 10.1177/0022034508328168
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the DSPP Gene Associated with Dentinogenesis Imperfecta Type II

Abstract: Hereditary dentin defects are divided into dentinogenesis imperfecta and dentin dysplasia. We identified a family segregating severe dentinogenesis imperfecta. The kindred spanned four generations and showed an autosomal-dominant pattern of inheritance. The proband was a child presenting with a severely affected primary dentition, with wide-open pulp chambers and multiple pulp exposures, resembling a DGI type III (DGI-III) pattern. We hypothesized that a mutation in the DSPP gene is responsible for this severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 20 publications
2
40
0
Order By: Relevance
“…10)2122232425262728293031323334. Seven genes including VWA1 , PTH1R , KDM1A and CSF1 have been related to abnormal cartilage and bone formations, with the CSF1 gene also linked to tenosynovial giant cell tumour3536373839. Interestingly, clinical situations have shown that patients with neurologic disorders exhibit localized bone changes and altered fracture healing with excessive callus formation40.…”
Section: Resultsmentioning
confidence: 99%
“…10)2122232425262728293031323334. Seven genes including VWA1 , PTH1R , KDM1A and CSF1 have been related to abnormal cartilage and bone formations, with the CSF1 gene also linked to tenosynovial giant cell tumour3536373839. Interestingly, clinical situations have shown that patients with neurologic disorders exhibit localized bone changes and altered fracture healing with excessive callus formation40.…”
Section: Resultsmentioning
confidence: 99%
“…[Kim et al, 2005a] Defects in this gene are the cause of many diseases such as dentinogenesis imperfecta type 1 (DGI1) and dentin dysplasia type 2 (DTDP2), both of which are autosomal dominant disorders. [Bhandari and Pannu, 2008; Lee et al, 2009] Researchers also found that mutations in the the DSPP gene lead to the production of abnormal DSPP-derived proteins or reduce the amount of these proteins in developing teeth. As a result, teeth have abnormally soft dentin.…”
Section: Discussionmentioning
confidence: 99%
“…DSPP: The first 31 amino acids of normal human DSPP (IPV) as well as the same fragment encoding the ISV (5), ITV (21), ILV (hypothetical), IPD (31), IPD3 (exon 3-skipping), IPF (21), and A15V (32) mutations in-frame with a 3' AgeI site were synthesized as oligonuclotides, double stranded by PCR and cloned into Gateway pENTR/D TOPO vector (Invitrogen, Carlsbad, CA). An identical approach was used to make normal and mutant (V-to-D) constructs using the first 31 amino acids of human OPN and DMP1.…”
Section: Methodsmentioning
confidence: 99%